Pico-Scale Digital PCR on a Super-Hydrophilic Microarray Chip for Multi-Target Detection - Qingyue Xian; Jie Zhang; Yu Ching Wong; Yibo Gao; Qi Song; Na Xu; Weijia Wen (Micromachines)
The technology of digital polymerase chain reaction (dPCR) is rapidly evolving, yet current devices often suffer from bulkiness and cumbersome sample-loading procedures. Moreover, challenges such as droplet merging and partition size limitations impede efficiency. In this study, we present a super-hydrophilic microarray chip specifically designed for dPCR, featuring streamlined loading methods compatible with micro-electro-mechanical systems (MEMS) technology. Utilizing hydrodynamic principles, our platform enables the formation of a uniform array of 120-pL independent reaction units within a closed channel. The setup allows for rapid reactions facilitated by an efficient thermal cycler and real-time imaging. We achieved absolute quantitative detection of hepatitis B virus (HBV) plasmids at varying concentrations, alongside multiple targets, including cancer mutation gene fragments and reference genes. This work highlights the chip’s versatility and potential applications in point-of-care testing (POCT) for cancer diagnostics.